High Signal-to-Noise Ratio Phonocardiogram using a Shielded PVDF Film Sensor - Vazquez, Karen; Cota, Juan; Sifuentes, Ernesto; Gonzalez, Rafael (Revista IEEE América Latina, 2016)
A shielded PVDF Film sensor has been used to obtain the Phonocardiogram (PCG) with high Signal-to-Noise Ratio (SNR). A very simple circuit is good enough to detect the first (S1) and the second (S2) sound of the PCG without using any digital signal processing technique. The mechanical coupling between the sensor and the subject determines the kind of signal detected. The sensor has been mounted on the membrane of a mechanical stethoscope in order to simplify the location of the best auscultation area on the chest. If the sensing area of the PVDF Film is in direct contact with the membrane (or the skin), the sensor detects the mechanical displacements of the heart contractions and respiration, so the PCG could not be detected. The best option to detect the S1 and the S2 is to leave an air gap between the sensor and the membrane. Despite using a shielded sensor, it is also necessary to shield electrically the circuit to reduce power line interference, which could not be filtered because it is in the frequency range of S1 and S2. The PCG and the lead II ECG have been measured on ten volunteers. Bland-Altman plots compares the time interval (beat-to-beat) between the peaks of the S1 and S2 with the RR interval of the ECG. The mean bias obtained is not greater than 0.75 ms, which is negligible. With the SNR obtained (>55 dB), it is possible to detect some valves diseases using a real-time comparison between the PCG and the ECG.